ORGANIZATIONAL AND LEGAL MECHANISMS OF PUBLIC ADMINISTRATION OF UKRAINE'S INTERNATIONAL COOPERATION IN CYBERSECURITY - Mialkovskyi, Danylo (Theory and Practice of Public Administration, 2019)
No state is capable of effectively alone counteracting the growth, number, scale, intensity, complexity of cyber incidents and cyber threats. This necessitates international cooperation in cybersecurity and cyber defense, joining forces and means to reduce the level of cyber threats to citizens, society and the state.The purpose of the article is to analyze the experience of Ukraine on the organizational and legal mechanisms of international cooperation in the field of cybersecurity in order to improve the relevant national mechanisms of public administration.One of the priorities of the national policy of national security, its integral component of cybersecurity, European and Euro-Atlantic integration is international cooperation, which should organically complement other areas of this policy.Adoption, implementation and application of international standards, in particular those of the European Union and NATO, are among the main ways of ensuring the effective functioning of the national cybersecurity system.In Ukraine, several state authorities, public and professional associations and organizations, business structures, and industry regulators are engaged in international cooperation in the field of cybersecurity. This requires their proper coordination.In order to increase the efficiency, effectiveness and validity of governmental decision-making, a Governmental Committee on European, Euro-Atlantic Integration, International Cooperation and Regional Development has been established within the Cabinet of Ministers of Ukraine, and designated ministrys' coordinators.But only six ministries cooperate within the framework of concluded agreements or international executive agreements of Ukraine within the framework of the Association Agreement with the European Union or within the framework of the 1997 Charter on a Distinctive Partnership.Cooperation with the EU is being carried out more and more through the ENISA. Cooperation with the NATO is being carried out through implementation the AJP-6, C‑M(2002)49 and AC/35-D/2004-REV3.Despite the adoption of the Law of Ukraine "On the Main Principles of sustainment of Cybersecurity of Ukraine ", Ukraine's capabilities do not meet the modern requirements sufficiently and need improvement:- organization of the national cybersecurity system;- receipt of international technical assistance by cyber-security entities, their proper coordination, applicability, appropriateness and adequacy of modern requirements, responsibility for their receipt and usability;- enhancement of professional skills not only of cybersecurity professionals but also of other employees of state bodies, enterprises and organizations;- protocols of interaction and information on cyber incidents both in Ukraine and foreign partners.